(untitled) (Nonconventional Technologies Review, 2021)
In the paper are analysed and determinate the optimum solution for making a bodywork for car used in formula student competition. In the first part of the paper the frontal element of a bodywork structure are presented. After the consideration of the generation of this element and positioned of this in rapport with the metallic structure of the car, it is determinate the solution with which can be made the support for generation of the bodywork. The milling machine is a component, which are used in laboratory for make different solution, and component of the car for formula student. An important aspect study in the paper are the deformation of the structure generated at different load forces using an FEA solution from INVENTOR software. Same of this element of the milling machine are generated by 3D printing and are analyse at the last part of the paper.